Decision-Support Framework for Location Planning of New Markets in the Retail Industry - Dhillon, Amandeep Kaur (2013)
Location selection can be a complex decision involving several factors at various levels and a good location can be a source of competitive advantage for the firm. Retail Location planning is still in its nascent stage within India, which has become the target of many international retailers, due to the huge potential it offers.